On the interplay between socioeconomic factors, personality and work environment in the pathogenesis of cardiovascular disease. - Theorell, Töres; Alfredsson, Lars; Knox, S.; Perski, Aleksander; Svensson, J.; Waller, D. (Scandinavian Journal of Work, Environment & Health, 1984)
This article summarizes some of the major findings in research on associations between psychosocial factors and cardiovascular illness. Methodological difficulties are discussed. Findings from some of the authors' own studies serve as illustrations. It is emphasized that an interplay between environmental and individual factors is of great importance. Personality factors relevant to the risk of cardiovascular illness may distort individual descriptions of the work environment. Cardiovascular risk factors such as cigarette smoking and repeated blood pressure elevations may be influenced by psychosocial factors. Lack of intellectual discretion at work, particularly if combined with excessive demands, may increase the risk of cardiovascular illness.